2015
DOI: 10.3171/2014.11.jns132348
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylfumarate alleviates early brain injury and secondary cognitive deficits after experimental subarachnoid hemorrhage via activation of Keap1-Nrf2-ARE system

Abstract: S ubarachnoid hemorrhage (SAH) is a critical neurosurgical phenomenon that is often coupled with several interrelated complications such as acute/delayed cerebral vasospasm, brain edema, obstructive/communicating hydrocephalus, diffuse/focal cerebral ischemia or infarction, and lasting cognitive deficits. 22,25 In China, the SAH-related morbidity rate is about 1.75 per 10,000. 30Despite recent progress in microsurgical and endovascular surgical techniques, the outcome of patients who suffer an SAH remains disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 30 publications
(29 reference statements)
0
67
0
1
Order By: Relevance
“…Once the cell encounters stimulation, such as oxidative stress, Nrf2 dissociates from Keapl, translocates into the nucleus, and binds to the ARE, subsequently inducing antioxidant enzyme expression, including NQO-1, HO-1, and SOD [25,32]. Mounting evidence from preclinical studies indicates that Nrf2 signaling activation can ameliorate SAH injury and that genetic elimination of Nrf2 aggravates SAH-induced secondary complications [59,60]. In fact, recent studies in other research areas have shown that SalB upregulates Nrf2 and HO-1 protein expression and enhances the ability of potential antioxidants [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Once the cell encounters stimulation, such as oxidative stress, Nrf2 dissociates from Keapl, translocates into the nucleus, and binds to the ARE, subsequently inducing antioxidant enzyme expression, including NQO-1, HO-1, and SOD [25,32]. Mounting evidence from preclinical studies indicates that Nrf2 signaling activation can ameliorate SAH injury and that genetic elimination of Nrf2 aggravates SAH-induced secondary complications [59,60]. In fact, recent studies in other research areas have shown that SalB upregulates Nrf2 and HO-1 protein expression and enhances the ability of potential antioxidants [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Hmox1 is one of the ARE-containing genes heavily regulated by Bach1 because the Hmox1 promoter is known to have a large number of ARE sequences to which Nrf2 can bind to induce its expression preferentially (Kensler et al, 2007). The enzymatic activity of Hmox1 involves catalyzing the degradation of heme to produce carbon monoxide, iron, and biliverdin, which are well known cellular antioxidant and anti-inflammatory agents known to induce neuroprotective effects (Otterbein et al, 2003). To determine the potential association of Bach1 nuclear export and Hmox1-mediated underlying neuroprotective mechanisms, we studied the neuroprotective effects of DMF and MMF against MPP ϩ toxicity in N27 rat dopaminergic cells with or without the presence of ZnPP, a widely used inhibitor of Hmox1 activity (Liu et al, 2014).…”
Section: Nrf2 Activation By Dmf and Mmf Is Associated With Bach1 Nuclmentioning
confidence: 99%
“…The enzymatic activity of Hmox1 involves catalyzing the degradation of heme to produce carbon monoxide, iron, and biliverdin, which are well known cellular antioxidant and anti-inflammatory agents known to induce neuroprotective effects (Otterbein et al, 2003). To determine the potential association of Bach1 nuclear export and Hmox1-mediated underlying neuroprotective mechanisms, we studied the neuroprotective effects of DMF and MMF against MPP ϩ toxicity in N27 rat dopaminergic cells with or without the presence of ZnPP, a widely used inhibitor of Hmox1 activity (Liu et al, 2014). As shown in Figure 3B, MPP ϩ induced significant cell death in N27 cells after 24 h, which was attenuated by pretreatment with either DMF (10 M) or MMF (10 M).…”
Section: Nrf2 Activation By Dmf and Mmf Is Associated With Bach1 Nuclmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term rodent recovery models are often used to explore post-SAH mechanisms that result in neurologic deficits [6][7][8]. Only recently has this work been extended to examine cognitive deficits [9][10][11][12][13]. Because post-SAH cognitive and memory deficits may persist for months to years in humans [3,14,15], there is need to optimize preclinical modeling to facilitate investigation of putative injury mechanisms and therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%